THE ASSESSMENT OF KNOWLEDGE REGARDING DIETARY PATTERN IN DIABETIC PREGNANT WOMAN - ZAHID, H; ARBAB, H; AMIR, Z; TASNEEM , SS; JABEEN, R (Biological and Clinical Sciences Research Journal, 2024)
Gestational diabetes mellitus (GDM) poses significant risks to maternal and fetal health, and proper dietary management is critical in mitigating these complications. In Pakistan, knowledge gaps and socio-economic barriers often limit adherence to recommended dietary practices. Objectives: To assess knowledge regarding dietary patterns among diabetic pregnant women in a tertiary care setting in Pakistan and identify barriers to effective dietary management. Methods: This cross-sectional study included 154 diabetic pregnant women receiving antenatal care at Sheikh Zayed Hospital, Lahore. Data were collected using a structured questionnaire assessing demographics, dietary knowledge, and perceived barriers. Descriptive and inferential analyses were performed using SPSS version 25, with a p-value <0.05 considered statistically significant. Results: Most participants (37.7%) had good knowledge of carbohydrate intake, while 26.0% demonstrated excellent understanding. Meal planning awareness was moderate in 44.2% of participants. Healthcare providers were the primary source of information (59.7%), yet barriers such as lack of knowledge (32.5%) and limited access to healthy foods (29.2%) were prevalent. Significant gaps in knowledge and practice were identified, particularly among underweight and overweight/obese women. Conclusion: This study underscores the need for structured dietary education programs tailored to the cultural and socio-economic context of Pakistan. Integrating nutritional counseling into antenatal care can enhance knowledge and improve dietary practices, reducing the risks associated with gestational diabetes.